2017
DOI: 10.1176/appi.ps.201600434
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antipsychotic Therapy: Association With Hospitalization and Medicare Spending Among Part D Enrollees With Schizophrenia

Abstract: Adherence to antipsychotics among Medicare Part D enrollees with schizophrenia was associated with significantly lower probability of psychiatric hospitalization and lower hospital expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
11
0
3
Order By: Relevance
“…Twenty studies reported on analyses of administrative databases [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] of which 17 were US based [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 13 analysed Medicaid data [24][25][26][27][28][29][30][31][32][33][34][35][36]. A conference abstract provided additional cost data for one of the studies…”
Section: Analysis Of Administrative Databasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty studies reported on analyses of administrative databases [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] of which 17 were US based [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 13 analysed Medicaid data [24][25][26][27][28][29][30][31][32][33][34][35][36]. A conference abstract provided additional cost data for one of the studies…”
Section: Analysis Of Administrative Databasesmentioning
confidence: 99%
“…The scope of these studies was generally limited to health care costs and some studies considered only hospital and pharmacy costs. Two studies contrasted the impact of adherence on mental and physical health care costs [26,40] and one study included criminal justice costs [27]. The complexity of these studies ranged from simple comparisons of costs across patient groups categorised by compliance to a sophisticated analysis of longer term costs which controlled for endogeneity using instrumental variables.…”
Section: Analysis Of Administrative Databasesmentioning
confidence: 99%
See 3 more Smart Citations